If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-2x+10=-7+5x+3
We move all terms to the left:
5x-2x+10-(-7+5x+3)=0
We add all the numbers together, and all the variables
5x-2x-(5x-4)+10=0
We add all the numbers together, and all the variables
3x-(5x-4)+10=0
We get rid of parentheses
3x-5x+4+10=0
We add all the numbers together, and all the variables
-2x+14=0
We move all terms containing x to the left, all other terms to the right
-2x=-14
x=-14/-2
x=+7
| -4c=-10−6c | | 5z+32-7=8z-1-6 | | x^2+9x-227=0 | | 111-u=249 | | 5x-2x-10=-7+5x+3 | | h3+32=37 | | -8p+10=-7p | | 6-2/9a=-14 | | m+22/4=10 | | -2k+8=-10k | | 24=-x+209 | | -10.8=-3.h | | 117=3*2^x | | 3x-5=12-5x | | 58=6s-26 | | -10t−8=-9t | | 5.42+19.6b=18.5b-5.69 | | 0.4x=76 | | -7h=8−9h | | -5u-172u+11= | | 3(u-59)=33 | | F(0)=6x+4 | | 6(u−86)=18 | | 16-7w=14-6w | | 5+14y=20 | | 3(f-12)+4.3=13.3 | | -z=-6z−10 | | 10=13-3v | | 3x+94=0 | | 4x-3x+5=20 | | 9b+3b+7=-17 | | -4v+20=-3(5v+8 |